Measurement of angular parameters from the decay $B^0 → K^{*0} μ^+ μ^-$ in proton-proton collisions at $\sqrt{s} = $ 8 TeV - CMS collaboration (2266 authors) (2018)
Angular distributions of the decay B0→K⁎0μ+μ− are studied using a sample of proton–proton collisions at s=8TeV collected with the CMS detector at the LHC, corresponding to an integrated luminosity of 20.5fb−1 . An angular analysis is performed to determine the P1 and P5′ parameters, where the P5′ parameter is of particular interest because of recent measurements that indicate a potential discrepancy with the standard model predictions. Based on a sample of 1397 signal events, the P1 and P5′ parameters are determined as a function of the dimuon invariant mass squared. The measurements are in agreement with predictions based on the standard model.